Forming of Polymer Nanofibers by a Pressurised Gyration Process - Mahalingam, Suntharavathanan; Edirisinghe, Mohan (Macromolecular rapid communications., 2013)
A new route consisting of simultaneous centrifugal spinning and solution blowing to form polymer nanofibers is reported. The fiber diameter (60–1000 nm) is shown to be a function of polymer concentration, rotational speed, and working pressure of the processing system. The fiber length is dependent on the rotational speed. The process can deliver 6 kg of fiber per hour and therefore offers mass production capabilities compared with other established polymer nanofiber generation methods such as electrospinning, centrifugal spinning, and blowing. A method is invented for the preparation of polymer nanofibers. The size distribution of the fibers can be tailored to suit. Using calculations where necessary, an explanation is given of the physical phenomenon of the new process which is also very competitive in comparison with the existing conventional methods, in particular yield and fiber size control.